Implementasi Intervensi Spiritual dalam Peningkatan Kesehatan Mental Pada Pasien Hemodialisa - Fadilah, Diby; Tri Rahayu, Henik (Pustaka Galeri Mandiri, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible illness that requires patients to undergo lifelong hemodialysis therapy. This condition not only affects physical health but also triggers various psychological problems, including anxiety, stress, depression, and loss of self-worth. This study aims to evaluate the effectiveness of spiritual interventions in improving the mental health of hemodialysis patients. The research employed a case study design involving a 36-year-old male patient receiving routine hemodialysis at Universitas Muhammadiyah Malang Hospital. Data were collected through interviews, observation, and documentation, and analyzed qualitatively using a descriptive approach. The spiritual intervention was implemented over seven days and included building a trusting relationship, practicing gratitude, identifying personal strengths, spiritual affirmation, self-reflection, and routine prayer based on the patient’s beliefs. Results indicated significant improvements in the patient’s emotional, spiritual, and behavioral responses. The patient became more relaxed, accepted his condition, displayed positive expressions, and showed improved sleep patterns. Spiritual intervention was found effective in reducing anxiety, enhancing self-worth, and restoring the patient’s sense of meaning in life. In conclusion, spiritual intervention is an effective strategy that should be integrated into holistic nursing care to support the mental well-being of hemodialysis patients.